Quantification of Extracellular α-Amylase Activity from Bacillus subtilis in a Strach Supplemented Medium Using Reducing Sugar Analysis - Yuyun Nisaul Khairillah; Marina Ratte (Universitas Labuhanbatu, 2026)
Background: α-Amylase is an extracellular enzyme responsible for the degradation of starch by cleaving α-1,4-glycosidic linkages, thereby producing shorter reducing sugars. This reaction holds significance due to the abundance, cost-effectiveness, renewability, and widespread use of starch as a raw material in numerous bioprocesses. In the context of industrial starch processing, the hydrolysis mediated by amylase is integral to the liquefaction and saccharification stages, which are critical in determining the efficiency of syrup production, brewing, baking, bioethanol production, and other processes reliant on starch. Methodology: This study aims to evaluate the extracellular α-amylase activity from Bacillus subtilis cultivated in nutrient broth supplemented with 1% (w/v) soluble starch. The culture was incubated at 37°C for 24 h under shaking conditions at 130 rpm and an initial medium pH of 7.0. The crude extracellular enzyme was obtained by centrifugation at 6,000 rpm for 20 min. α-Amylase activity was determined using the 3,5-dinitrosalicylic acid (DNS) assay by measuring reducing sugars released from soluble starch hydrolysis, with maltose as the calibration standard. The enzyme activity was determined in U/mL by spectrophotometric analysis at 550 nm. Findings: The maltose standard curve produced the regression equation y = 0.7849x + 0.0938 and an R² value of 0.9732. The B. subtilis culture grown in starch-supplemented nutrient broth showed a mean absorbance of 2.3915 and an α-amylase activity of 0.116 U/mL. These results showed that B. subtilis secreted detectable extracellular α-amylase under the tested conditions, although the activity was low. Contribution: The addition of starch contributed to enzyme induction because starch functions as both a substrate-related carbon source and a signal for amylolytic enzyme production. Therefore, nutrient broth supplemented with 1% starch can be used as a simple medium for preliminary extracellular α-amylase production by B. subtilis